Reconstruction of Moon Phases and Period in The Book of Enoch on Islamic Astronomy Perspective - Youla Afifah Azkarrula; Ahmad Syifaul Anam (Asy-Syari'ah, 2024)
The Book of Enoch presents an explanation of Moon in a different way when compared to many ancient manuscripts. The periods of the Moon associated with the Moon phases are illustrated in a unique way that, in first glance, requires a deep understanding. This explanation is different with what science has explained nowadays. To begin with, the previous research of this subject on the Book of Enoch is out to dated. Therefore, this research conducts a new approach to examine the Book of Enoch using Islamic perspective where this study is rare to conduct. This study utilizes qualitative research with content analysis to gain the answer in depth. This research also uses triangulation method to investigate the data and obtain the validity of the results. Overall, the Moon phase in the Book of Enoch has the same understanding as the modern science. The Book of Enoch describes implicitly the appearance of Moon in the northern hemisphere. The explanation of Enoch lunar-day in each month is followed by the Urfi Islamic calendar. Then the statement about “once the month is 28-day” is based on the using of Callippic cycle in Charles opinion while in the author’s opinion that the Book of Enoch shows the sidereal month cycle. In addition, the theory which has been adopted by Islamic astronomy has a strong relationship with this manuscript since it is believed that this manuscript is attributed to Prophet Enoch or Idris.